Polarization-Insensitive Reflective Metasurfaces for Highly Efficient Generation of OAM Beams - Bai, Xudong (Frontiers in Physics, 2020)
The polarization-insensitive reflective metasurfaces constructed from hexagonal-ring units along with honeycomb lattice are proposed for the efficient generation of converged orbital angular momentum (OAM) waves. The proposed unit is with very succinct structure constructed from a hexagonal-ring patch along with a hexagonal metallic reflector, which could achieve a polarization-insensitive response to the incident waves, when binding furtherly with the hexagonal lattice. Through the topology optimization of the unit arrangement, two reflective metasurfaces stimulating the first-order and the second-order OAM beams are numerically designed, which may find useful in radio communications and radar applications.